2020
DOI: 10.4088/jcp.20l13419
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Psychiatric Emergency Department Visits due to Suicidal Ideation and Suicide Attempts During the COVID-19 Pandemic in Madrid, Spain

Abstract: R ecent reports indicate that the current coronavirus disease 2019 (COVID-19) pandemic is generating substantial increases in the global burden of depression, anxiety, and acute stress disorders. 1,2 Potential explanations include fear of contagion, grief for the death of loved ones, social isolation due to confinement measures, and stress due to negative economic consequences in both the short and long terms, among others. One major concern is that this unprecedented health and social crisis will also bring a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
39
4
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 0 publications
8
39
4
4
Order By: Relevance
“…We have no reason to believe that this proportion decreased during the period of lockdown, especially as there was no reduction in the availability of mental health staff in either centre and satellite assessment units were available for a short time in both centres to provide assessment for patients fit to be seen there. Also, our findings are similar to those reported from other hospitals in England ( Chen et al., 2020 ), in Paris during the first four weeks of lockdown ( Pignon et al., 2020 ), in Madrid during the early stages of the pandemic ( Hernandez-Calle et al., 2020 ) and in presentations of individuals with suicidal ideation to emergency departments in the USA ( Smalley et al., 2020 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We have no reason to believe that this proportion decreased during the period of lockdown, especially as there was no reduction in the availability of mental health staff in either centre and satellite assessment units were available for a short time in both centres to provide assessment for patients fit to be seen there. Also, our findings are similar to those reported from other hospitals in England ( Chen et al., 2020 ), in Paris during the first four weeks of lockdown ( Pignon et al., 2020 ), in Madrid during the early stages of the pandemic ( Hernandez-Calle et al., 2020 ) and in presentations of individuals with suicidal ideation to emergency departments in the USA ( Smalley et al., 2020 ).…”
Section: Discussionsupporting
confidence: 90%
“…An early report from Paris, France, indicated reduced referrals to mental health services for attempted suicide in the city in the first four weeks following Pignon et al., 2020 ). A Spanish study from a general hospital Madrid indicated a major reduction in individuals presenting to the emergency department with suicidal ideation and suicide attempts in March and April following development of the pandemic ( Hernandez-Calle et al., 2020 ). In the Mid-West of the USA a very marked reduction in presentations to emergency departments for suicidal ideation was identified in the month following ‘stay at home’ orders introduced on March 24 th 2020 compared with the same period in 2019 ( Smalley et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…We have no reason to believe that this proportion decreased during the period of lockdown, although there was some reduction in the availability of mental health staff in one centre. Also, our findings are similar to those being reported anecdotally from other hospitals in England, in Paris during the first four weeks of lockdown (Pignon et al, 2020), in Madrid during the early stages of the pandemic (Hernandez-Calle et al, 2020) and in presentations of individuals with suicidal ideation to emergency departments in the USA (Smalley et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…An early report from Paris, France, indicated reduced referrals to mental health services for attempted suicide in the city in the first four weeks following lockdown (Pignon et al, 2020). A Spanish study from a general hospital Madrid indicated a major reduction in individuals presenting to the emergency department with suicidal ideation and suicide attempts in March and April following development of the pandemic (Hernandez-Calle et al, 2020). In the Mid-West of the USA a very marked reduction in presentations to emergency departments for suicidal ideation was identified in the month following ‘stay at home’ orders introduced on March 24 th 2020 compared with the same period in 2019 (Smalley et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This report concluded: “It would be inappropriate to derive increasing mental illness rates from these data.” (Techniker Krankenkasse, 2020: 44; our translation) Also, suicide rates and suicide attempt rates in various countries do not seem to have risen compared to pre-pandemic times (e.g. Hernandez-Calle et al, 2020, John et al, 2020, Leske et al, 2020). Whether these trends will hold in further infection or lockdown phases, remains to be seen.…”
Section: Discussionmentioning
confidence: 82%